รูปแบบภาคีความร่วมมือการให้บริการอากาศยานพยาบาลไทย: Collaboration Pattern in Thailand Aero Medical Service - Thadadech, Jitisak; Trangan, Yuthana; Thaiarry, Piphat; Kasemkitwatana, Saipin (Asian Health, Science and Technology Reports, 2011)
Deep impact of disasters to human life, we need supportive of Aero Medical Service (AMS) to save life and minimize disability. Phenomenological Study and 21 indepth interview of qualitative selected participants was conducted. Result of the study on collaboration pattern of Thailand AMS found that The Emergency Medical Institute of Thailand (EMIT) is main taking charge from AMS policy within the Emergency Medical Act B.E.2551 (2008). It has created Memorandum of Understanding (MOU) tool in networking a unique medical collaborative outsourcing, providing and training specialized emergency flight care to public health personnel for Sky Doctor mission. This collaborative pattern is working only under MOU contract between EMIT and public private health service providers, included police and military forces. Being center of collaboration, EMIT gain 8 partnerships and 101 aircrafts, which identified into 3 categories: Fully Equipment type, Assembly type and Fixes Wing type. The capabilities of the air medical resources will give benefit for life saving consideration during emergency or critical occurrences like disaster for the sickness and severely injured in remote and disaster area equitable, effective and efficient.